Religious Behavior and Parenting Patterns of Students of Muhammadiyah University of North Sumatra Fisipol Semester VI T.A 2016-2017 - Rasta Kurniawati Br. Pinem (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Religious Behavior and Parenting Patterns of Students of Muhammadiyah University of North Sumatra Fisipol Semester VI T.A 2016-2017